Fibroblasts can induce thymocyte positive selection in vivo. - Hugo, P (1993)
During development in the thymus, thymocytes bearing alpha beta T-cell receptors are selected to mature if the receptors they bear are able to interact in some way with major histocompatibility complex (MHC) proteins expressed on thymic stromal cells. It has been shown that thymus cortical epithelial cells are usually the cells presenting the MHC molecules involved in this process of so-called positive selection. Here we tested the ability of fibroblasts to mediate positive selection in vivo. Fibroblasts transfected with the genes for the MHC I-Ab proteins were injected intrathymically into irradiated H-2k animals reconstituted with H-2bxk F1 fetal liver cells. Eight weeks later, the recipient mice were immunized and shown to contain peptide-specific I-Ab-restricted T cells. This demonstrates the ability of I-Ab-transfected fibroblasts to participate in positive selection. Thus a cell type that is not specialized to process and present antigens in the context of MHC class II molecules can mediate positive selection when transfected with an appropriate MHC molecule. The data also support the idea that the ability to mediate positive selection may not be limited to thymic cortical epithelium.